2017
DOI: 10.1371/journal.pone.0182278
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic vinculin is not essential for embryonic development in zebrafish

Abstract: The formation of multicellular tissues during development is governed by mechanical forces that drive cell shape and tissue architecture. Protein complexes at sites of adhesion to the extracellular matrix (ECM) and cell neighbors, not only transmit these mechanical forces, but also allow cells to respond to changes in force by inducing biochemical feedback pathways. Such force-induced signaling processes are termed mechanotransduction. Vinculin is a central protein in mechanotransduction that in both integrin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…S5 A), predicted to produce a truncated protein lacking its actin-binding domain. These mutants did not survive to adulthood, a finding consistent with other recent studies of vclb function (Cheng et al, 2016; Han et al, 2017; unpublished data). However, we found that vclb mutants did not exhibit strong delays in AV EC migration and valve formation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…S5 A), predicted to produce a truncated protein lacking its actin-binding domain. These mutants did not survive to adulthood, a finding consistent with other recent studies of vclb function (Cheng et al, 2016; Han et al, 2017; unpublished data). However, we found that vclb mutants did not exhibit strong delays in AV EC migration and valve formation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…It is now important to determine whether the extensive list of proteins implicated in mechanosensing at the cell-cell contacts actually coexists or rather represent specificities of each model, as well as their role in tensiondependent stabilization of cell-cell adhesion in vivo. Strikingly, Vinculin knockout in worms (Barstead and Waterston, 1989), flies (Alatortsev et al, 1997), fish (Han et al, 2017), and mouse (Xu et al, 1998) display either no or rather weak phenotypes as compared to the loss of core components of the cell-cell adhesion machinery, arguing against an essential role for Vinculin in regulating AJs' integrity and dynamics. Nonetheless, it remains possible that other mechanosensitive components can functionally compensate for Vinculin loss of function and cooperate to ensure tension-dependent cell-cell adhesion reinforcement; thus, further work will now be required to discriminate between these two possibilities.…”
Section: Durotaxismentioning
confidence: 99%
“…Based on in vitro experiments, vinculin has been shown to be a potent mechanotransducer, however this has not seemed to be the case in vivo (Goldmann, 2016;Martino et al, 2018;Spanjaard and de Rooij, 2013). While the in vitro manipulation of vinculin at FAs have profound consequences on the forces generated by these junctions, the in vivo function of vinculin has remained unclear because its genetic lossof-function in worms, flies and fish elicit weak or no phenotypes (Alatortsev et al, 1997;Barstead and Waterston, 1989;Han et al, 2017;Xu et al, 1998). In mice, the loss of vinculin results primarily in cardiac defects (Xu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%